Clinical efficacy of the Toll-like receptor 9 agonist cobitolimod using patient-reported-outcomes defined clinical endpoints in patients with ulcerative colitis. Issue 10 (October 2018) - Atreya, Raja; Reinisch, Walter; Peyrin-Biroulet, Laurent; Scaldaferri, Franco; Admyre, Charlotte; Knittel, Thomas; Kowalski, Jan; Neurath, Markus Friedrich; Hawkey, Christopher
Abstract: Background: The Toll-like-receptor 9 (TLR-9) agonist cobitolimod (DIMS0150, Kappaproct ® ) is a promising therapeutic option for ulcerative colitis (UC) patients. Aims: The objectives of this post-hoc analysis using the COLLECT study data was to investigate the clinical effects of cobitolimod using patient-reported-outcomes (PRO) defined endpoints. Methods: Dual topical administration of cobitolimod was studied in a randomised, multicentre clinical trial named COLLECT in moderate-to-severe UC patients. Symptomatic remission (SR) was studied in 104 patients based on their e-diary records and was defined as absence of blood in stool and a mean daily stool frequency (SF) < 4. Results: SR was achieved at week 4 in 17.1% of cobitolimod vs. 5.9% of placebo treated patients (p = 0.13), at week 8 in 35.7% vs. 17.6% (p = 0.07), and at week 12 in 38.6% vs. 17.6% (p = 0.04) of the patients, respectively. SR rates with cobitolimod and placebo in anti-TNFα experienced patients were smaller but with a broadly similar relative effect-size to anti-TNFα naïve patients. Clinical efficacy was higher in patients with moderate compared to severe disease. Conclusions: Application of the Toll-like-receptor 9 (TLR-9) agonist cobitolimod is able to induce remission as assessed by PRO measures in UC patients with moderate-to-severe activity as well as in anti-TNFα experienced and naïve patients supporting the overall efficacy of the substance.